(untitled) (Faridpur Medical College Journal, 2013)
Planar and SPECT bone scintigraphy has played a major role in the staging of many cancers such as breast and prostate cancer, as well as in orthopedics. Integrated diagnostic CT combined with SPECT has helped improve localization and characterization of skeletal lesions, improving diagnostic confidence and helping management decisions, over traditional SPECT. A major advantage has been improved characterization of indeterminate bone lesions and differentiation of benign from malignant lesions due to additional CT information. In this treatise the role of SPECT-guided CT for evaluating foci of increased bone metabolism classified as indeterminate of SPECT in cancer patients is reviewed. Using this approach, the diagnostic confidence in differentiating malignant from benign bone lesions should better with the fused SPECT/CT image than with separate sets of bone scintigraphic and CT images. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16895 Faridpur Med. Coll. J. 2013;8(1): 31-33